Brokering anime: how to create a Japanese animation business bridge between Japan and India - Mihara, R (2017)
This thesis ethnographically examines the globalising of the Japanese animation (anime) business in the context of the creative industries, of Japan’s politico-economic position in Asia, and of brokerage. Influencing the world’s entertainment, creators, and youth culture, anime is one of the crucial lenses through which one can examine Japan’s presence in the world. Despite the prevalent assumption that anime is globally popular, this thesis highlights the precarious performance of the anime business overseas, and examines it through an entrepreneurial anime business project trying to bridge the Japanese anime business into the Indian market. The ethnography of the project centres on its founding entrepreneur, focusing on how he tried to ally with insiders in the Japanese anime sector and the Indian market. The thesis’s 12-month fieldwork accompanied his business in Japan (Tokyo) and India (Delhi), revealing a perspective of the entrepreneur as a broker who intermediates between the discrepant positions of his stakeholders to keep his business afloat. It also highlights the two most critical discrepancies: the dichotomies of art versus commerce (one of the central topics in creative industries studies) and the ‘Japanese’ versus ‘Indian’ ways of doing business (one of the prominent topics in Japan’s political economy vis-à-vis the Asian region). The ethnography found the entrepreneur’s liminal dual agency in bridging, blurring and reorienting the dichotomies was a driving force carrying his business forward. This thesis counterbalances previous anthropological studies on the creative industries (including anime) that tend to advocate the centrality of creators and fans, by focusing on the businessperson in a creative project. It also suggests that the broker is a crucial point of reference when examining how to create workable compromises between art and commerce, and allowing Japanese and Asian businesspeople to get along. The thesis also enhances our understanding of entrepreneurship by revealing most of its function as brokerage.